(untitled) (Revista Cocar, 2024)
O estudo analisa hermenêuticamente Obra dos Gaiatos da Guarda/Portugal valorizando a sua ação educativa/formativa (e assistencial) às crianças/jovens, no arco histórico do Estado Novo e dar contributos à H.ª da Educação e H.ª das Instituições Educativas. A Obra integrava Escola do Gaiatos (experiência ensino noturno para jovens entre 12 a 20 anos) e Instituto S. Miguel-Outeiro (colégio de internato/externato) de ensino particular. Manuseamos várias fontes documentais (Espólio/Arquivo Liga dos Servos de Jesus, Centro Assistência Social, Instituto S. Miguel), arquivo distrital, biblioteca municipal e imprensa regional que nos permitiram construir a memória daquela Obra, numa visão sintética do seu itinerário sociopedagógico. Realizámos análise descritiva à Escola dos Gaiatos (1945-74) e Instituto (1974-78) em relação movimento de alunos, cujos resultados confirmam a grande aceitação/procura que tinha. Palavras-chave: Obra dos Gaiatos da Guarda; Assistência educativa; ensino particular. Abstract The study analyzes the Guard/Portugal’s hermeneutically Work of the Gayeties by valued their educational/formative (and assistential) action to children/young, in the New State Historic arc, and to make contributions to the H.’ of Education and H.E. of Educational Institutions. The Work integrated Gayeties School (experience night teaching for youth between 12 to 20 years) and Institute S. Miguel-Outeiro (boarding school and external) of private teaching. We handled several documentary sources (Estate/Archive League of Jesus Servants, Social Assistance Center, S. Miguel Institute), district file, municipal library and regional press that allowed us to build the memory of that Work, in a synthetic insight into its sociopedagogical itinerary. We conducted descriptive analysis to the School of Gayeties (1945-74) and Institute (1974-78) in relation to movement of students, the results of which confirm the great acceptance/demand it had. Keywords: Work of the Guard Gayeties; Education Assistance; particular teaching.